Gender Based Adjacency Pairs Analysis Found in Barbie: the Movie and Its Translation - Deta Maria Sri Darta; Rindang Widiningrum; Ervin Suryaningsih; Erio FanggidaE (Journal of Language and Literature, 2025)
Conversation Analysis is a part of Discourse Analysis that is usually used to analyze conversations in human interaction. Since movies can be considered as a piece of literature made to resemble real life, this theory is adapted to discuss how characters in the movies interact to communicate. The different styles of communication between characters of different genders is a gripping subject to explore. Therefore, the purpose of this research was to analyze conversations between female-male, female-female, and male-male characters in the movie Barbie.   Since the data gathered were utterances in conversation, the adjacency pairs in the conversation were analyzed to see the pattern. The finding showed that there were differences in the types of adjacency pairs used between females and males in conversation. Female-Female conversations in Barbie tend to have more variety in types of adjacency pairs used if compared to Male-Male conversations. Meanwhile, the conversation between different genders, if initiated by a female (Female-Male conversations), was likely to have numerous types of adjacency pairs in contrast to if initiated by a male (Male-Female conversations). When the Indonesian subtitle was analyzed, there were no types of adjacency pairs modified through translation.   The findings also revealed that certain types of adjacency pairs were found only in specific gender conversations. Furthermore, the discussion revealed that gender plays a role in the choice of adjacency pairs employed.